Resistance to Pyrenophora teres f. teres and P. teres f. maculata in Canadian Barley Genotypes. Issue 1 (28th November 2016) - Akhavan, Alireza; Strelkov, Stephen E.; Kher, Swaroop V.; Askarian, Homa; Tucker, James R.; Legge, William G.; Tekauz, Andy; Turkington, T. Kelly
Abstract : The fungi Pyrenophora teres Drechs. f. teres Smedeg. ( Ptt ) and Pyrenophora teres Drechs. f. maculata Smedeg. ( Ptm ) cause the net (NFNB) and spot forms (SFNB) of net blotch of barley ( Hordeum vulgare L.). The reaction of a collection of barley genotypes previously identified as resistant to NFNB and/or SFNB in western Canada was assessed against seven isolates each of Ptt and Ptm . These included isolates recently collected from western Canada plus reference isolates frequently used in resistance breeding programs. Experiments were conducted under greenhouse conditions, with the second and third leaves of each plant rated on disease reaction scales of 1 to 10 ( Ptt ) or 1 to 9 ( Ptm ) 1 wk after inoculation. The NFNB resistance in the cultivars 'Vivar' and 'CDC Helgason' was overcome by two and four of the Ptt isolates, respectively. 'AAC Synergy' was resistant to all Ptt isolates examined, although two caused disease severities of 4.6 and 5.0, suggesting some adaptation to the resistance in this cultivar. The breeding lines TR 253, CI 9819, and TR 236 were the most resistant to Ptt, with average disease severities of almost 3.0. Resistance to SFNB in 'CDC Meredith' was overcome by all Ptm isolates tested, while 'Cerveza', 'Major', and AAC Synergy were resistant to all of the isolates. Among the breeding lines, TR 236 was the most resistant to Ptm, with an average rating score of 3.9. The identification of isolates virulent on cultivars classified as "resistant" highlights the need for integrated disease management approaches to avoid net blotch resistance breakdown in western Canada.